The EIS book : managing and preparing environmental impact statements - Eccleston, Charles H. (CRC Press, 2014)
"The National Environmental Policy Act (NEPA) requires that ALL federal agencies prepare Environmental Impact Statements (EIS) for any proposal that may significantly affect the quality of the human environment. They generally take more than a year to prepare, have an extensive public participation component, and require substantial collection of original data. An Assessment can generally be completed in a few months. A company, institution, dedicated environmental professional, or federal agency generally is involved with preparation of both assessments and impact statements. This book helps agencies prepare EISs by providing step-by-step direction for navigating the EIS process"--